The Influence of Social Media Marketing, Price Perception, and Product Quality on Purchasing Decisions for Citra Body Scrub Product in Surabaya - Rr. Rachmalia Nadia Rizqina; Hery Pudjoprastyono; Nanik Hariyana (Universitas KH. Abdul Chalim Mojokerto, 2025)
The Indonesian cosmetic industry has begun to develop from year to year. However, the development of the cosmetic industry in Indonesia is also followed by internal and external challenges. The existence of competition with foreign markets, especially China, has made the cosmetic industry in Indonesia begin to be affected. If it is not immediately addressed, the Indonesian cosmetic industry can be defeated by the foreign cosmetic industry. This study aims to determine and analyze the influence of social media marketing variables, price perception, and product quality on purchasing decisions for Citra body scrub products in the city of Surabaya. Samples were taken using purposive sampling technique with a total of 112 respondents. Data collection was carried out by distributing questionnaires. The scale used in the questionnaire is a Likert scale of 1-5. The results of the questionnaire answers were analyzed using SmartPLS software. This study tests the hypothesis using the Structural Equation Model (SEM) technique with the Partial Least Square (PLS) analysis method. The results of this study indicate that social media marketing has a positive and significant effect on purchasing decisions. Price perception has a positive and significant effect on purchasing decisions. Product quality has a positive and significant effect on purchasing decisions.